New orchids in the flora of Vietnam X (Orchidaceae, Orchidoideae, tribe Orchideae, Epidendroideae, tribes Gastrodieae, Arethuseae, Cymbidieae, and Vandeae) - Averyanov, Leonid V.; Nguyen, van Canh; Vuong, Truong Ba; Quang, Bui Hong; Nguyen, Khang Sinh; Le, Tuan Anh; Binh, Tran Duc; Maisak, Tatiana V.; Nguyen, Cuong Huu (Phytotaxa, 2025)
The paper presents new data on the orchid diversity of Vietnam obtained mainly during the fieldwork of 2023–2024, as well as a result of investigation of the herbarium and garden collections of Russia and Vietnam. It includes five species new to science, namely Cleisostoma truongquanii, Cymbidium bavuongii, Hemipilia uniflora, Micropera vietnamensis, Robiquetia binhii, and one variety, Biermannia averyanovii var. micrantha. Six species, Biermannia brachystachys, Cleisostoma nangongense, Coelogyne cumingii, Eulophia bicallosa, Gastrodia fontinalis, and Schoenorchis seidenfadenii are reported for Vietnam at first. For each of the studied taxa, their types, relevant synonyms, studied specimens, ecology and phenology (within Vietnam), distribution, preliminarily assessed conservation status, brief taxonomic notes and illustrations are provided. For the newly described taxa, morphological descriptions and notes on etymology are included. In addition, new nomenclature combinations, Panisea lecongkietii (Vuong, Aver. & Q.T.Truong) Aver., Biermannia brachystachys (Schltr.) Aver., Thrixspermum arunachalensis (A.N.Rao) Aver., and Thrixspermum jainiana (S.N.Hegde & A.N.Rao) Aver. are proposed. Based on available literature data and currently presented data the orchid flora of Vietnam includes 1382 species belonging to 184 genera.